PENGARUH PENINGKATAN JUMLAH PEMBAWA PESAN TERHADAP TINGKAT KOGNITIF RESPONDEN PADA MEDIA AUDIO - Setiadi Umar; Agus Hasan Pura P.A (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
In the advertising, a certain style of executing messages can be encountered based on testimonial evidence. As regards testimonial evidence, the marketing party involved can employ several endorsers or make use of only one in advertisements to deliver the message. The focus of study is on the extent to which people's cognitive response are affected by an increase in the number of endorsers and by the differentiation in the perceived quality of the commercials presented in audio-based commercials, a type of commercial that can only be heard by the respondents who cannot see the actual speaker's face.